The Economic Well-Being of Never- and Ever-Married Single Mother Families: A Cross National Comparison - Ann Nichols-Casebolt; Judy Krysik (Luxembourg Income Study (LIS), 1995)
This study addresses the effect of marital status on economic well-being by comparing the economic situation of never- and ever-married single mother families in the United States, Australia, Canada, and France. The paper presents cross-national, descriptive and analytic data on poverty levels, sources of income, and basic demographic characteristics. The findings are discussed within the context of identifying factors that may suggest policy strategies for addressing the economic risks faced by never-married single mother families.
Keywords: 330; Alleinerziehende; Lebensstandard; Australien; Kanada; Frankreich; USA